Utopia or Dystopia: Connecting Begum Rokeya and Bernardine Evaristo - Shihab, Md. Nuruddin Pier (Muslim English Literature, 2025)
This research paper attempts to bridge the voices of Begum Rokeya, a British Indian writer, and Bernardine Evaristo, a contemporary British writer. One of the primary texts is Rokeya’s “Sultana’s Dream,” and another is Bernardine Evaristo’s “The White Man’s Liberation Front.” This article follows the qualitative-descriptive method to analyze two primary texts with reference to Thomas More’s concept of “Utopia” and John Stuart Mill’s framework of “Dystopia.” Many scholars claim these stories to be feminist utopias. However, the purpose of the study is to create an analogy between these stories by pointing out some discrepancies in these utopias. Nevertheless, this research does not posit any anti-feminist stance and does not question the celebration of womanhood in the two stories. It shows that none of the stories expresses any ideal solution for equality and harmony. The stories present men and women in opposition to each other instead of narrating them as partners. The questions they raise on patriarch are correct, but that never means it ought to be replaced with matriarchy. This research does not defend patriarchy but finds that the models of women’s superiority presented in the two stories are dystopian. As the stories have a universal appeal with a similar essence, both of them create a bridge between the voices of local and global women’s rights. Still, the paper suggests the settings as dystopian because of the lack of a tone for equality.